KAJIAN PEMBUATAN PEDA IKAN TERI (Stolephorus sp.) BERDASARKAN LAMA FERMENTASI DAN KONSENTRASI GARAM SEBAGAI RANCANGAN PEMBUATAN LKS PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Mellisa, Novyona Ayu; Mahadi, Imam; Sayuti, Irda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research to determine the quality of peda anchovies (Stolephorus sp) treated with length of fermentation and salt concentration for the student worksheet design that was conducted in March 2017. This research was carried out by two phases: the field research and design student worksheet (LKS). Research experiments were conducted using a completely randomized design (CRD) factorial 4x3 with 3 replicates in order to obtain 36 units of the experimental design. Parameters observed include protein content, fat content, pH value and organoleptic value which include aroma, color, texture and taste. The results showed that the length fermentation and salt concentration significant effect on protein content, fat content, pH value in the peda anchovies (Stolephorus sp). Where the best fermentation anchovy is found in T4G1 treatment (20 days length fermentation with 15% salt concentration) with protein content of 7.9%, fat content of 0.17%, pH value of 5.96 and the most preferred organoleptic by the panelists because it has a very tasty taste, scented-peda began to sharply aroma, the texture of fish that have been destroyed with a gray-brown color. Results from the study are used as a design student worksheet (LKS) on the subjects of biology in high school.Key words: Length of fermentation, salt concentration, Peda Anchovies and Student Worksheet.